English Teacher’ Strategies to Teach Listening of ADHD in Senior High School - Alya Syahlani Saragih; Diah Safitri Armin (Jurnal Ragam Pengabdian, 2026)
This study investigated the strategies used by an English teacher to improve the listening skills of a student with Attention Deficit Hyperactivity Disorder (ADHD) in an inclusive senior high school classroom. Using a qualitative case study design, data were collected through semi-structured interviews and classroom observations involving one English teacher who taught a student with ADHD. The data were analyzed using thematic analysis. The findings revealed six major themes: the teacher’s adaptation process, the student’s characteristics and responses during listening activities, the use of simple and repetitive instructions, the use of visual media and animation, challenges in managing distractions, and the development of the student’s focus skills. The teacher implemented various adaptive strategies, including individual guidance, repeated instructions, simplified explanations, audio-visual materials, and supportive teacher and student interactions. These strategies helped increase the student’s engagement and participation in listening activities despite ongoing attention difficulties. The study also found that the teacher relied primarily on personal teaching experience rather than formal training in inclusive education. The findings highlight the importance of adaptive teaching practices and the need for professional development programs to better prepare teachers to support students with ADHD in inclusive EFL classrooms.